The Effectiveness and Contribution of Entertainment Tax to Sukabumi Regency Local Revenue Receipts in 2019-2022 - Arifin, Arifin; Yenni, Yenni (SEIKO : Journal of Management & Business, 2023)
The goal of this study was to determine the effectiveness and contribution of Entertainment Tax revenue to Sukabumi Regency's Original Regional Revenue from 2019 to 2022. The data collection technique used was documentation, and the data analysis techniques used were descriptive data analysis, effectiveness analysis, and contribution analysis. According to the study's findings, the implementation of the entertainment tax on Sukabumi Regency's Regional Original Income in 2019-2022 was extremely effective, with an average annual effectiveness of 111%. With the highest level of effectiveness of Entertainment Tax receipts in 2019, which was 227%. The lowest level of entertainment tax revenue effectiveness in 2022 was 41%. The contribution of entertainment tax to Sukabumi Regency's Regional Original Income in 2019-2022 Keywords: Entertainment Tax, Effectiveness, Contribution